Epidemiology, Outcomes, and Trends of Patients With Sepsis and Opioid-Related Hospitalizations in U.S. Hospitals*. Issue 12 (December 2021) - Alrawashdeh, Mohammad; Klompas, Michael; Kimmel, Simeon; Larochelle, Marc R.; Gokhale, Runa H.; Dantes, Raymund B.; Hoots, Brooke; Hatfield, Kelly M.; Reddy, Sujan C.; Fiore, Anthony E.; Septimus, Edward J.; Kadri, Sameer S.; et al.
Abstract : OBJECTIVES: Widespread use and misuse of prescription and illicit opioids have exposed millions to health risks including serious infectious complications. Little is known, however, about the association between opioid use and sepsis. DESIGN: Retrospective cohort study. SETTING: About 373 U.S. hospitals. Patients: Adults hospitalized between January 2009 and September 2015. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Sepsis was identified by clinical indicators of concurrent infection and organ dysfunction. Opioid-related hospitalizations were identified by the International Classification of Diseases, 9th Revision, Clinical Modification codes and/or inpatient orders for buprenorphine. Clinical characteristics and outcomes were compared by sepsis and opioid-related hospitalization status. The association between opioid-related hospitalization and all-cause, in-hospital mortality in patients with sepsis was assessed using mixed-effects logistic models to adjust for baseline characteristics and severity of illness. The cohort included 6, 715, 286 hospitalizations; 375, 479 (5.6%) had sepsis, 130, 399 (1.9%) had opioid-related hospitalizations, and 8, 764 (0.1%) had both. Compared with sepsis patients without opioid-related hospitalizations ( n = 366, 715), sepsis patients with opioid-related hospitalizations ( n = 8, 764) were younger (mean 52.3 vs 66.9 yr) and healthier (mean Elixhauser score 5.4 vs 10.5), had more bloodstream infections from Gram-positive and fungal pathogens (68.9% vs 47.0% and 10.6% vs 6.4%, respectively), and had lower in-hospital mortality rates (10.6% vs 16.2%; adjusted odds ratio, 0.73; 95% CI, 0.60–0.79; p < 0.001 for all comparisons). Of 1, 803 patients with opioid-related hospitalizations who died in-hospital, 928 (51.5%) had sepsis. Opioid-related hospitalizations accounted for 1.5% of all sepsis-associated deaths, including 5.7% of sepsis deaths among patients less than 50 years old. From 2009 to 2015, the proportion of sepsis hospitalizations that were opioid-related increased by 77% (95% CI, 40.7–123.5%). CONCLUSIONS: Sepsis is an important cause of morbidity and mortality in patients with opioid-related hospitalizations, and opioid-related hospitalizations contribute disproportionately to sepsis-associated deaths among younger patients. In addition to ongoing efforts to combat the opioid crisis, public health agencies should focus on raising awareness about sepsis among patients who use opioids and their providers. Abstract : Supplemental Digital Content is available in the text.